p90RSK-MAGI1 Module Controls Endothelial Permeability by Post-translational Modifications of MAGI1 and Hippo Pathway - Abe, Rei J.; Savage, Hannah; Imanishi, Masaki; Banerjee, Priyanka; Kotla, Sivareddy; Paez-Mayorga, Jesus; Taunton, Jack; Fujiwara, Keigi; Won, Jong Hak; Yusuf, Syed Wamique; Palaskas, Nicolas L.; Banchs, Jose; et al. (Frontiers in Cardiovascular Medicine, 2020)
Previously, we reported that post-translational modifications (PTMs) of MAGI1, including S741 phosphorylation and K931 de-SUMOylation, both of which are regulated by p90RSK activation, lead to endothelial cell (EC) activation. However, roles for p90RSK and MAGI1-PTMs in regulating EC permeability remains unclear despite MAGI1 being a junctional molecule. Here, we show that thrombin (Thb)-induced EC permeability, detected by the electric cell-substrate impedance sensing (ECIS) based system, was decreased by overexpression of dominant negative p90RSK or a MAGI1-S741A phosphorylation mutant, but was accelerated by overexpression of p90RSK, siRNA-mediated knockdown of magi1, or the MAGI1-K931R SUMOylation mutant. MAGI1 depletion also increased the mRNA and protein expression of the large tumor suppressor kinases 1 and 2 (LATS1/2), which inhibited YAP/TAZ activity and increased EC permeability. Because the endothelial barrier is a critical mediator of tumor hypoxia, we also evaluated the role of p90RSK activation in tumor vessel leakiness by using a relatively low dose of the p90RSK specific inhibitor, FMK-MEA. FMK-MEA significantly inhibited tumor vessel leakiness at a dose that does not affect morphology and growth of tumor vessels in vivo. These results provide novel insights into crucial roles for p90RSK-mediated MAGI1 PTMs and the Hippo pathway in EC permeability, as well as p90RSK activation in tumor vessel leakiness.